Acute myocardial injury is common in patients with COVID-19 and impairs their prognosis. Issue 15 (30th April 2020) - Wei, Jia-Fu; Huang, Fang-Yang; Xiong, Tian-Yuan; Liu, Qi; Chen, Hong; Wang, Hui; Huang, He; Luo, Yi-Chun; Zhou, Xuan; Liu, Zhi-Yue; Peng, Yong; Xu, Yuan-Ning; et al.
Abstract : Objective: We sought to explore the prevalence and immediate clinical implications of acute myocardial injury in a cohort of patients with COVID-19 in a region of China where medical resources are less stressed than in Wuhan (the epicentre of the pandemic). Methods: We prospectively assessed the medical records, laboratory results, chest CT images and use of medication in a cohort of patients presenting to two designated covid-19 treatment centres in Sichuan, China. Outcomes of interest included death, admission to an intensive care unit (ICU), need for mechanical ventilation, treatment with vasoactive agents and classification of disease severity. Acute myocardial injury was defined by a value of high-sensitivity troponin T (hs-TnT) greater than the normal upper limit. Results: A total of 101 cases were enrolled from January to 10 March 2020 (average age 49 years, IQR 34–62 years). Acute myocardial injury was present in 15.8% of patients, nearly half of whom had a hs-TnT value fivefold greater than the normal upper limit. Patients with acute myocardial injury were older, with a higher prevalence of pre-existing cardiovascular disease and more likely to require ICU admission (62.5% vs 24.7%, p=0.003), mechanical ventilation (43.5% vs 4.7%, p<0.001) and treatment with vasoactive agents (31.2% vs 0%, p<0.001). Log hs-TnT was associated with disease severity (OR 6.63, 95% CI 2.24 to 19.65), and all of the three deaths occurred in patients with acute myocardial injury. Conclusion: Acute myocardial injury is common in patients with COVID-19 and is associated with adverse prognosis.